Autonomy Support, Basic Psychological Needs and Well-Being in Mexican Athletes. - López Walle, Jeanette M.; Balaguer Solá, Isabel; Castillo Fernández, Isabel María; Tristán Rodríguez, José Leandro (2012)
Based on Basic Needs Theory, one of the mini-theories of Self-determination Theory (Ryan & Deci, 2002), the present study had two objectives: (a) to test a model in the Mexican sport context based on the following sequence: perceived coach autonomy support, basic psychological needs satisfaction, and psychological well-being, and b) to analyze the mediational effect of the satisfaction of perceived coach autonomy support on indicators of psychological well-being (satisfaction with life and subjective vitality). Six hundred and sixty-nine young Mexican athletes (Boys = 339; Girls = 330; Mage = 13.95) filled out a questionnaire assessing the study variables. Structural equations analyses revealed that perceived coach autonomy support predicted satisfaction of the basic psychological needs for autonomy, competence, and relatedness. Furthermore, basic need satisfaction predicted subjective vitality and satisfaction with life. Autonomy, competence and relatedness partially mediated the path from perceived coach autonomy support to psychological well-being in young Mexican athletes.